DNA Fragmentation and Vitamin K2 Levels in Sperm Maturation and Apoptosis: Fragmentasi DNA dan Tingkat Vitamin K2 dalam Pematangan Sperma dan Apoptosis - Ismael, Khaleel Ibrahim; Al-Maliki, Rehab Shafiq; Al-Tameem, Amina Akram (Indonesian Journal on Health Science and Medicine, 2025)
Background: There is mounting evidence that vitamin K2 (menaquinones) plays a role as a hormone and transcriptional regulator, which has raised interest in its possible impact on male reproductive health. The vitamin K series as a whole has a long history of therapeutic use around the world. Because of its essential function in removing damaged germ cells and preserving the quality of spermatozoa, vitamin K may have an antioxidant impact that is advantageous to spermatogenesis, a process regulated by apoptosis. Aim of the study: Association of DNA fragmentation as an apoptotic marker and Vit K2 levels with sperm maturation. Patients, materials and methods: Sixty-seven infertile men were included in this Cross-sectional study. All the patients underwent Vit K assessment by ELISA, Seminal fluid analysis according to WHO 2021 and DNA fragmentation test using aniline blue staining. Results: The study found highly significant inverse correlation between vit K2 level and DNA fragment proportion of the study sample of semen but there is inverse insignificant correlation of fragmentation with sperm motility while other semen parameters showed insignificant positive correlation including concentration, vitality and normal morphology. Progressive motile sperms (AB) and immotile sperms (D) were found with high significant difference between sperm DNA fragmentation and non-sperm DNA fragmentation. Also, there were no significant differences between infertile men with and without sperm DNA fragmentation in age, smoking, alcohol conception, varicocele and type of infertility.  Conclusions: The findings revealed a highly significant negative correlation between vitamin K2 levels and sperm with DNA fragmentation, as well as a highly significant positive correlation between vitamin K2 levels and sperm without DNA fragmentation. The findings indicate that vitamin K2 may play a protective function in protecting sperm DNA integrity. Highlights : Vitamin K2 Protects Sperm DNA – Higher K2 levels correlate with lower DNA fragmentation. Minimal Impact on Motility – Fragmentation shows weak links to sperm motility and other parameters. No Link to Lifestyle – Factors like smoking and varicocele show no significant effect. Keywords : Vit K, Apoptosis, DNA Fragmentation, Biomarker, ROS